2003
DOI: 10.1177/0891988703252177
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Behavioral Disturbances and Pattern of Psychotropic Medication Use in Five Skilled Nursing Facilities

Abstract: There are several treatment options for behavioral disturbances (BDs) in dementia. However, the choice of a specific psychotropic agent is directed by personal preferences and local community practice patterns. We examined the relationship between common clusters of BDs and the use of different classes of psychotropic agents in our community. A cross-sectional study of 430 long-term care residents from 5 nursing homes was undertaken. The Behavior Measurement Scale (BMS) was used to measure the frequency of BDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In another American study patients with clinically relevant symptoms used antipsychotic drugs or benzodiazepines more frequently (Ramadan et al ., 2003). A Norwegian study found a significant association between the type of drug and the psychiatric symptoms for which it had been dispensed; psychotic symptoms were strongly associated with the use of antipsychotic medication, whereas depression and anxiety were strongly associated with antidepressant, anxiolytic and sedative drug use (Selbaek et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another American study patients with clinically relevant symptoms used antipsychotic drugs or benzodiazepines more frequently (Ramadan et al ., 2003). A Norwegian study found a significant association between the type of drug and the psychiatric symptoms for which it had been dispensed; psychotic symptoms were strongly associated with the use of antipsychotic medication, whereas depression and anxiety were strongly associated with antidepressant, anxiolytic and sedative drug use (Selbaek et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In general, antipsychotic medication was more frequently prescribed in patients with at least one neuropsychiatric symptom (Lindesay et al ., 2003; Selbaek et al ., 2006). One study showed no association between different types of agitation and specific type of medication (Ramadan et al ., 2003), but in a Norwegian study there was an association between the type of psychotropic drug and the psychiatric symptoms for which it had been prescribed (Selbaek et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…32 The general concern with 3 classes of these drugs (antianxiety, sedative/hypnotic, and antipsychotic) 38 is that the rates of use may be excessive and/or clinically unjustified, to the degree that they are used to chemically restrain residents. 39 Thus, these 3 classes of psychoactive drugs were used as a QI.…”
Section: Quality Indicators (Qis)mentioning
confidence: 99%
“…SIB was associated with prescribed benzodiazepines, but not with anti-psychotics or anti-depressants. Psychotropic medications are often prescribed to manage behavioural disturbances in dementia (Ballard self-injurious behaviour et al, 2001;Hartikainen et al, 2003;Holmquist et al, 2003;Margallo-Lana et al, 2001;Ramadan et al, 2003). They are also commonly used in institutional settings to manage SIB (Pies and Popli, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Different causal factors have been postulated and the aetiology of SIB is likely to be multifactorial, representing a final common pathway (Draper et al, 2002a;Hall and O'Connor, 2004). Dementia type, dementia severity, psychotropic drugs and measures to restrain the patient are of practical importance to the management of SIB in nursing home patients Draper et al, 2001;Margallo-Lana et al, 2001;Draper et al, 2002a;Draper et al, 2002b;Holmquist et al, 2003;Ramadan et al, 2003;Low et al, 2004).…”
Section: Introductionmentioning
confidence: 99%